MODEL PEMBELAJARAN TEMATIK DALAM PENINGKATAN MINAT BELAJAR SISWA PADA MASA KENORMALAN BARU DI SDIT TASMIRA PANCORAN MAS DEPOK - Siti Widiastuti (el-Moona: Jurnal Ilmu Pendidikan Islam, 2021)
This study aims to analyze the thematic learning model in increasing student interest in learning during the new normal at SDIT Tasmira. This research uses a qualitative approach with a phenomenological study design, namely a qualitative research method that analyzes or examines phenomena that are visible or can be observed with the five senses. Data collection techniques in this study were carried out by observation, interviews and documentation. The targets of this observation were students, teachers and school principals at SDIT Tasmira Pancoran Mas, Depok, West Java. This study used structured interviews and the respondents in this interview were the teachers and principals of SDIT Tasmira Pancoran Mas, Depok, West Java. Retrieval of data through documents can be done by researchers by observing photo documentation of students, teachers at SDIT Tasmira school. These results indicate that the learning interest of SDIT Tasmira Pancoran Mas students, Depok, West Java experienced a positive increase in the new normal.